2014
DOI: 10.1177/1352458514543811
|View full text |Cite
|
Sign up to set email alerts
|

Cortical thickness and surface area relate to specific symptoms in early relapsing–remitting multiple sclerosis

Abstract: We found that cortical thickness, but not cortical surface area, is affected in early RRMS. We identified specific structural correlates to the main clinical symptoms in early RRMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
78
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 265 publications
(420 reference statements)
10
78
0
1
Order By: Relevance
“…thalamus, caudate, and pallidum) (Cifelli et al 2002;Filippi and Agosta 2010;Vercellino et al 2009). Disability has been linked specifically to cortical thinning in the frontal (including anterior cingulate gyrus) and temporal lobes (for EDSS) (Charil et al 2007;Nygaard et al 2015), occipital region (for visual Functional System Scores) (Calabrese et al 2007) as well as grey matter loss in the striatum (for Fatigue Severity Status Scale) (Calabrese et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…thalamus, caudate, and pallidum) (Cifelli et al 2002;Filippi and Agosta 2010;Vercellino et al 2009). Disability has been linked specifically to cortical thinning in the frontal (including anterior cingulate gyrus) and temporal lobes (for EDSS) (Charil et al 2007;Nygaard et al 2015), occipital region (for visual Functional System Scores) (Calabrese et al 2007) as well as grey matter loss in the striatum (for Fatigue Severity Status Scale) (Calabrese et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is considerable evidence that both normal appearing white matter (Kutzelnigg et al 2005;Bodini et al 2009) and gray matter (De Stefano et al 2003;Sailer et al 2003;Ceccarelli et al 2008) may be affected in early RRMS patients, and associated with specific symptoms, like cognition and fatigue (Sepulcre et al 2009;Nygaard et al 2014). Cerebellar pathology is also related to eye movements disorders, as recently shown in a study of antisaccades and cognition in early MS patients (Kolbe et al 2014 …”
Section: Discussionmentioning
confidence: 94%
“…They also underwent a thorough neuropsychological assessment (Nygaard et al 2014). Results of the auditory 3 seconds' version of the Paced Auditory Serial Addition Test (PASAT) (Gronwall 1977) performed by the patients, and wSDMT (Smith Aron 1982) performed by all participants, are reported.…”
Section: Clinical Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural imaging studies focusing on the quantification of atrophy have reported an association of fatigue severity with atrophy in the thalamus and a number of different cortical gray matter regions (superior frontal and inferior parietal gyrus, parietal lobe) in patients with relapsing-remitting MS [90, 91]. Yaldizli et al found an association between callosal atrophy and fatigue and cognitive performance in a large cohort of MS patients with various disease courses [92], and Nygaard et al reported a relation between regionally smaller cortical surface areas and volumes and higher depression and fatigue scores in relapsing-remitting MS patients [93]. Although Gobbi et al did not find an association between white matter atrophy and lesion distribution [94], a previous study by Sepulcre et al suggested a correlation between T2 lesion load and fatigue severity and between fatigue scores and gray matter atrophy in frontal regions [95].…”
Section: Clinical Correlates and Biological Mechanismsmentioning
confidence: 99%